The last town ebook - Crouch, Blake (Wayward Pines, 2022)
The final book of the smash-hit Wayward Pines trilogy from the New York Times bestselling author of Dark Matter, Recursion, and Upgrade What’s inside was a nightmare. What’s outside is a thousand times worse. Welcome to Wayward Pines, the last town. Secret Service agent Ethan Burke arrived in Wayward Pines, Idaho, three weeks ago. In this town, people are told who to marry, where to live, where to work. No one is allowed to leave; even asking questions can get you killed. But Ethan has discovered the astonishing secret of what lies beyond the electrified fence that surrounds Wayward Pines and protects it from the terrifying world beyond. And now that secret is about to come storming through the fence to wipe out this last, fragile remnant of humanity. The Last Town at last pitches Ethan Burke and his fellow residents into all-out war against the forces outside the town’s gates—and in doing so delivers every bit the riotously horrific, breathlessly action-packed conclusion that the Wayward Pines trilogy deserves.